x-(-7)=-18 x+(-8)=-21 2x-(-15)=-9 -3x+(-3)=-15 -3.(2x+6)-13=-37 (3x/2-5)+(-10)=-12 Giả

x-(-7)=-18

x+(-8)=-21

2x-(-15)=-9

-3x+(-3)=-15

-3.(2x+6)-13=-37

(3x/2-5)+(-10)=-12

Giải giúp em nhanh với mn

2 bình luận về “x-(-7)=-18 x+(-8)=-21 2x-(-15)=-9 -3x+(-3)=-15 -3.(2x+6)-13=-37 (3x/2-5)+(-10)=-12 Giả”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
    x – (- 7)= – 18
    => x + 7 = – 18
    => x = – 18 – 7 = – 25
    x + (- 8)= – 21
    => x – 8 = – 21
    => x = – 21 + 8
    => x = – 13
    2x – (- 15) = 9
    => 2x + 15 = 9
    => 2x = 9 – 15
    => 2x = – 6
    => x = – 6 : 2 = – 6/2
    – 3x + (- 3) = – 15
    => – 3(x + 1) = – 15
    => x + 1 = – 15 : (- 3)
    => x + 1 = 5
    => x = 5 – 1 = 4
    – 3 . (2x + 6) – 13 = – 37
    => – 3 . (2x + 6) = – 37 + 13
    => – 3 . 2(x + 3) = – 24
    => – 6(x + 3) = – 24
    => x + 3 = – 24 : (- 6)
    => x + 3 = 4
    => x = 4 – 3 = 1
    ((3x)/2 – 5) + (- 10)= – 12
    => ((3x)/2 – 5) = – 12 + 10
    => (3x)/2 – 5 = – 2
    => (3x)/2 = – 2 + 5
    => (3x)/2 = 3
    => 3x : 2 = 3
    => 3x  = 3 . 2 = 6
    => x  = 6 : 3 = 2
    \color{orange}text{Xin hay nhất ạ}
    \color{lightblue}text{KhoaOvO}
     

    Trả lời

Viết một bình luận

Câu hỏi mới